2014
DOI: 10.1007/s40272-014-0075-3
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Utilization of Reporting Pathways for Adverse Events Following Immunization: Online Survey Among Pediatricians in Russia and Germany

Abstract: Pediatricians play a key role in the post-marketing surveillance of vaccine safety. The lack of training represents a missed opportunity. There may be a role for professional societies to improve vaccine safety training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…It has been shown that the degree of formal training in vaccine safety has a direct impact on the quality of vaccine safety reporting [86]. Experience has shown that vaccinology may best be taught by infectious disease specialists who need to be proficient in infectious disease epidemiology, immunology, virology and microbiology as well as vaccine safety research and communication.…”
Section: Textbox 3 How Young Doctors May Learn To Listen To the Patient Voice In Vaccine Safetymentioning
confidence: 99%
“…It has been shown that the degree of formal training in vaccine safety has a direct impact on the quality of vaccine safety reporting [86]. Experience has shown that vaccinology may best be taught by infectious disease specialists who need to be proficient in infectious disease epidemiology, immunology, virology and microbiology as well as vaccine safety research and communication.…”
Section: Textbox 3 How Young Doctors May Learn To Listen To the Patient Voice In Vaccine Safetymentioning
confidence: 99%
“…The exact timing of observations will be key to distinguishing cause and effect: In the QM setting for example, the presence of fever was positively correlated with the physician's decision to prescribe antibiotics [68]. Unfortunately, pediatricians and general practitioners tend to be unaware of existing reporting standards [69]. The majority of vaccine safety reports may thus be lost or misdirected unless further training and assistance are provided [69].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, pediatricians and general practitioners tend to be unaware of existing reporting standards [69]. The majority of vaccine safety reports may thus be lost or misdirected unless further training and assistance are provided [69]. Physicians using the VACC-Tool may overcome such barriers by submitting anonymized reports of verified adverse events, directly to regulatory agencies.…”
Section: Discussionmentioning
confidence: 99%